2019
DOI: 10.3390/s19040822
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Calibration Method for Photonic Mixer Device Solid-State Array Lidars

Abstract: The photonic mixer device (PMD) solid-state array lidar, as a three-dimensional imaging technology, has attracted research attention in recent years because of its low cost, high frame rate, and high reliability. To address the disadvantages of traditional PMD solid-state array lidar calibration methods, including low calibration efficiency and accuracy, and serious human error factors, this paper first proposes a calibration method for an array complementary metal–oxide–semiconductor photodetector using a bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…It can be obviously figured out that the proposed method has better performance on range accuracy compared with methods in [13,17,26]. Although the mean distance error shows no distinct improvement compared with method in [19], the proposed method has better Compared with the method in [42], the method proposed in this paper effectively reduced the error in the distance range of 0.5-5 m. Meanwhile, the adaptivity under different environments improved a lot. Table 4 gives the detailed performance comparison results of the two methods.…”
Section: Lens Distortion Correctionmentioning
confidence: 78%
See 3 more Smart Citations
“…It can be obviously figured out that the proposed method has better performance on range accuracy compared with methods in [13,17,26]. Although the mean distance error shows no distinct improvement compared with method in [19], the proposed method has better Compared with the method in [42], the method proposed in this paper effectively reduced the error in the distance range of 0.5-5 m. Meanwhile, the adaptivity under different environments improved a lot. Table 4 gives the detailed performance comparison results of the two methods.…”
Section: Lens Distortion Correctionmentioning
confidence: 78%
“…The test results are illustrated in Figure 14. Compared with the method in [42], the method proposed in this paper effectively reduced the error in the distance range of 0.5-5 m. Meanwhile, the adaptivity under different environments improved a lot. Table 4 gives the detailed performance comparison results of the two methods.…”
Section: Lens Distortion Correctionmentioning
confidence: 93%
See 2 more Smart Citations
“…Sun et al [22] purposed a new array geometry calibration method for underwater compact arrays to improve the robustness and accuracy of the calibration results. Zhai et al [23] researched a calibration method for an array complementary metal-oxide-semiconductor photodetector using a black-box calibration device and an electrical analog delay method to address the disadvantages of traditional PMD (photonic mixer device) solid-state array lidar calibration methods. Through the above research, it can be concluded that the calibration of sensor arrays is helpful to improve their accuracy and practicability.…”
Section: Introductionmentioning
confidence: 99%